Bullying in the Military: Implications and Remedies - Tsewu, Bulelani (Scientia militaria : South African journal of military studies, 2025)
While it is not part of the profile of a soldier to bully other soldiers, the nature of the military and its status as a social institution make soldiers vulnerable to the events of bullying. Such vulnerability comes about because of the structural inequalities - especially hierarchical relationships - that characterise military service. It bears emphasising that soldiers operate in a unique and robust environment with a rigid and uncompromising hierarchical rank structure with specified roles and career fields. Soldiers however do not forfeit basic human rights, and should therefore be protected from treatment that degrades their sense of self-worth. The study on which this article reports, examined the possible impact of bullying in the South African National Defence Force, while also considering legal remedies available to victims of bullying. To this end, a review of relevant literature and discussions with some soldiers and defence civilians who were located in various bases throughout the Republic of South Africa were undertaken. It was concluded that bullying exists in the South African National Defence Force, and if left unchecked, may hamper morale, military discipline, and the operational effectiveness of the defence force. South Africa is a democratic country that is founded on, inter alia, the advancement of human dignity and the rule of law.2 Importantly, the Constitution of the Republic of South Africa, (1996) stipulates that the South African National Defence Force (SANDF) is the only lawful military force in the country,3 and it is to be disciplined.4 SANDF members (soldiers, sailors, and airmen) are citizens in uniform, and are fully entitled to enjoy the rights in the Bill of Rights.5 Section 2(g) of the Defence Act (No. 42 of 2002) enjoins the SANDF to respect the fundamental rights of all persons. Bullying however exists in the SANDF, and it affects several fundamental rights.6 The focus in the current article was on the rights to dignity,7 fair labour practices,8 and not to be subjected to cruel, inhuman or degrading treatment,9 since these rights are the most affected by bullying in the SANDF. The primary aim of the research was to evaluate the concept of bullying in the military, especially with regard to its possible effect on the victims and operational readiness of the defence force.